KEPRIBADIAN GURU IDEAL DALAM KITAB ADABU AL ALIM WA AL MUTA’ALLIM The Ideal Teacher Personality In Adabu Al Alim Wa Al Muta’allim Book - M. Sabiq Kamalul Haq (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
The phenomena of education in the recent time shows that teachers’ characters has only activated at class room and most of the academician emphasize on the cognitive rather than affection and moral aspect. However, there are many previous studies on the teachers’ characters. This research aims to explore the Islamic education teachers’ characters on the book Adabu al Alim wa al Muta’allim written by KH.Hasyim Asy’ari. This study uses a theory of big five personality. The result of this study shows that the teacher’s personality type in such book is dominantly characterized by conscientiousness, for instance the teacher must be diligent, tidy, responsible, persistent, obeying the rules and norms of religion and society. The essence of teacher’s personality in the book is that the teacher must have knowledge and apply it in their life as well as down to earth. In addition, the number of Sufis in the book represents the omission of egoistic behaviors.